Clustered slumping in the northern South China Sea: Implications for chronology and geohazards - Yin Lu; Ed L. Pope; Qiliang Sun; Michael Strasser (Global and Planetary Change, 2025)

Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

Association between large neutral amino acids and white matter hyperintensities in middle-aged adults at varying metabolic risk - Cherry Youn; Marie L. Caillaud; Yanrong Li; Isabelle A. Gallagher; Barbara Strasser; Hirofumi Tanaka; Andreana P. Haley (Brain Imaging and Behavior, 2024)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

BCL-2 protein family: attractive targets for cancer therapy - Deeksha Kaloni; Sarah T Diepstraten; Andreas Strasser; Gemma L Kelly (Apoptosis, 2023)
Acquired resistance to cell death is a hallmark of cancer. The BCL-2 protein family members play important roles in controlling apoptotic cell death. Abnormal over-expression of pro-survival BCL-2 family members or abnormal reduction of pro-apoptotic BCL-2 family proteins, both resulting in the inhibition of apoptosis, are frequently detected in diverse malignancies. The critical role of the pro-survival and pro-apoptotic BCL-2 family proteins in the regulation of apoptosis makes them attractive targets for the development of agents for the treatment of cancer. This review describes the roles of the various pro-survival and pro-apoptotic members of the BCL-2 protein family in normal development and organismal function and how defects in the control of apoptosis promote the development and therapy resistance of cancer. Finally, we discuss the development of inhibitors of pro-survival BCL-2 proteins, termed BH3-mimetic drugs, as novel agents for cancer therapy.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

A subaqueous hazard map for earthquake-triggered landslides in Lake Zurich, Switzerland - M. Strupler; L. Danciu; M. Hilbe; K. Kremer; F. S. Anselmetti; M. Strasser; S. Wiemer (Natural Hazards, 2018)

Challenges in operationalizing the water–energy–food nexus - J. Liu; H. Yang; C. Cudennec; A.K. Gain; H. Hoff; R. Lawford; J. Qi; L. de Strasser; P.T. Yillia; C. Zheng (Hydrological Sciences Journal, 2017)

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

Reduced nicotine reward in obesity: cross-comparison in human and mouse - Julie A. Blendy; Andrew Strasser; Carrie L. Walters; Kenneth A. Perkins; Freda Patterson; Robert Berkowitz; Caryn Lerman (Psychopharmacology, 2005)

Metarhizium anisopliae, a potential agent for the control of grape phylloxera - M. Kirchmair; L. Huber; M. Porten; J. Rainer; H. Strasser (BioControl, 2004)

Molecular cloning of cDNA encoding N-acetylglucosaminyltransferase II from Arabidopsis thaliana - R. Strasser; H. Steinkellner; M. Borén; F. Altmann; L. Mach; J. Glössl; J. Mucha (Glycoconjugate Journal, 1999)

Apoptosis and autoimmune disease - L. A. O'Reilly; A. Strasser (Inflammation Research, 1999)

Settlement cues in successive developmental stages of the ghost shrimps Callichirus major and C. islagrande (Crustacea: Decapoda: Thalassinidea) - K. M. Strasser; D. L. Felder (Marine Biology, 1998)

Sex Hormones Differentially Regulate Isoforms of UDP-Glucuronosyltransferase - Simone I. Strasser; Sheree A. Smid; Maurice L. Mashford; Paul V. Desmond (Pharmaceutical Research, 1997)